cGAS-STING, inflammasomes and pyroptosis: an overview of crosstalk mechanism of activation and regulation - Liu, Jingwen; Zhou, Jing; Luan, Yuling; Li, Xiaoying; Meng, Xiangrui; Liao, Wenhao; Tang, Jianyuan; Wang, Zheilei (Cell communication and signaling, 2024)
Background Intracellular DNA-sensing pathway cGAS-STING, inflammasomes and pyroptosis act as critical natural immune signaling axes for microbial infection, chronic inflammation, cancer progression and organ degeneration, but the mechanism and regulation of the crosstalk network remain unclear. Main body of the abstract Cellular stress disrupts mitochondrial homeostasis, facilitates the opening of mitochondrial permeability transition pore and the leakage of mitochondrial DNA to cell membrane, triggers inflammatory responses by activating cGAS-STING signaling, and subsequently induces inflammasomes activation and the onset of pyroptosis. Meanwhile, the inflammasome-associated protein caspase-1, Gasdermin D, the CARD domain of ASC and the potassium channel are involved in regulating cGAS-STING pathway. Importantly, this crosstalk network has a cascade amplification effect that exacerbates the immuno-inflammatory response, worsening the pathological process of inflammatory and autoimmune diseases. Given the importance of this crosstalk network of cGAS-STING, inflammasomes and pyroptosis in the regulation of innate immunity, it is emerging as a new avenue to explore the mechanisms of multiple disease pathogenesis. Therefore, efforts to define strategies to selectively modulate cGAS-STING, inflammasomes and pyroptosis in different disease settings have been or are ongoing. In this review, we will describe how this mechanistic understanding is driving possible therapeutics targeting this crosstalk network, focusing on the interacting or regulatory proteins, pathways, and a regulatory mitochondrial hub between cGAS-STING, inflammasomes, and pyroptosis. Short conclusion This review aims to provide insight into the critical roles and regulatory mechanisms of the crosstalk network of cGAS-STING, inflammasomes and pyroptosis, and to highlight some promising directions for future research and intervention.